2014
DOI: 10.3844/ajavsp.2014.65.70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance Assessment of Subclinical Mastitis in Milk Samples From Selected Dairy Farms

Abstract: This study was conducted in order to determine the prevalence and bacteriological assessment of subclinical mastitis and antimicrobial resistance of bacterial isolates from dairy cows in different farms around Selangor, Malaysia. A total of 120 milk samples from 3 different farms were randomly collected and tested for subclinical mastitis using California Mastitis Test (CMT), as well as for bacterial culture for isolation, identification and antimicrobial resistance. The most prevalent bacteria was Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Acinetobacter sp. was isolated from mastitis in our study, as supported by Marimuthu et al (2014). Similary, Proteus sp.…”
Section: Resultssupporting
confidence: 60%
“…Acinetobacter sp. was isolated from mastitis in our study, as supported by Marimuthu et al (2014). Similary, Proteus sp.…”
Section: Resultssupporting
confidence: 60%
“…In contrast to our study, Sumathi et al [14], Dubal et al [15], Ranjan et al [16], Harini and Sumathi [17], Kurjogi and Kaliwal [18], Abd-Elrahman [19] and Jeykumar et al [20] observed E. coli being second in prevalence following staphylococci. However, Marimuthu et al [21] found 21% of organisms isolated to be Bacillus spp. which was totally absent in our study and other studies mentioned earlier.…”
Section: Prevalence Of Different Microorganismsmentioning
confidence: 99%
“…The main treatment of mastitis is commonly administered by intramammary infusion of an ointment or intramuscular or intravenous injection of antibiotics, such as streptomycin, ampicillin, cloxacillin, penicillin, and tetracycline [8]. However, the treatment is anticipated to become problematic in the near future owing to the rapid increase in antibiotic-resistant pathogens [20, 21]. Therefore, seeking for treatments alternative to antibiotic therapy is required.…”
Section: Introductionmentioning
confidence: 99%